Classification of Philosophical Sciences of Ahmad Tashkoprizade - Urolbek Berkinovich, Ergashev (International Journal of Psychosocial Rehabilitation, 2020)
In the history of the development of scientific knowledge, there has been a constant organic connection between the question of the classification of sciences and philosophy and its relation to other sciences. In the Middle Ages, some fields that many scientists in the East considered to be science are not seen as science today. For a long time, the concepts of knowledge, science, subject, and art were harmonized. An example of this can be shown in “Mawduot al-Ulum” by Ahmad Tashkoprizade. This article describes the historical significance of the work and the peculiarities of the classification of philosophical sciences through a comparative analysis. There is also information about the role of Tashkoprizade in the history of the classification of philosophical sciences and its differences from other thinkers in this regard. During the reading of the article, a clear idea of the main features of the classification of philosophical sciences of Tashkoprizadeemerges.